Citation Classics in Social Policy Journals. (November 2016) - Powell, Martin
Abstract: This article is the first to explore the concept of 'Citation classics' in social policy by examining the articles published in five leading social policy journals that have 50 or more Web of Science (WoS) citations. It introduces the concept of citation analysis; discusses 'citation classics' in terms of definitions, measures, journals and databases; examines the literature on other social sciences, and particularly social work; and then focuses on the empirical material of citation classics in social policy journals. It finds 79 articles with 50 or more citations. Over half of the articles were written by authors based in the UK at the time of publication, with most of the others from the rest of Europe. About two‐thirds were classified as 'conceptual', and about a quarter were quantitative. Surprisingly few were qualitative or reviews. Roughly one‐third of articles were mainly focused on a particular service area, with the leading areas being employment, health, social care/community care or long‐term care. For the setting or focus of the study, nearly two‐thirds were comparative, while about a quarter were based on the UK. The leading topic was welfare regimes (14 articles). The limitations to this analysis include focusing on five social policy journals, and ignoring other outputs such as books; and the problem of determining what influence these articles have on the field of social policy. However, exploring the neglected area of citation classics in social policy provides one way of determining intellectual significance within the discipline.